2010
DOI: 10.1002/glia.21022
|View full text |Cite
|
Sign up to set email alerts
|

Microglia promote colonization of brain tissue by breast cancer cells in a Wnt‐dependent way

Abstract: Although there is increasing evidence that blood-derived macrophages support tumor progression, it is still unclear whether specialized resident macrophages, such as brain microglia, also play a prominent role in metastasis formation. Here, we show that microglia enhance invasion and colonization of brain tissue by breast cancer cells, serving both as active transporters and guiding rails. This is antagonized by inactivation of microglia as well as by the Wnt inhibitor Dickkopf-2. Proinvasive microglia demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
210
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(220 citation statements)
references
References 58 publications
4
210
2
4
Order By: Relevance
“…Consequently, the invading breast cancer cells exhibit specific neural characteristics which enable them to penetrate into the brain tissue; thereby, highly activated GABA expression increases their proliferative capacity, particularly within the pre-metastatic niches as the preferable microenvironment. In this context, an active communication between invading cancer cells, astrocytes and microglia in the Bhosting^brain parenchyma has been identified representing an essential part of the successful cancer cell nesting and metastatic process [49][50][51][52].…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Consequently, the invading breast cancer cells exhibit specific neural characteristics which enable them to penetrate into the brain tissue; thereby, highly activated GABA expression increases their proliferative capacity, particularly within the pre-metastatic niches as the preferable microenvironment. In this context, an active communication between invading cancer cells, astrocytes and microglia in the Bhosting^brain parenchyma has been identified representing an essential part of the successful cancer cell nesting and metastatic process [49][50][51][52].…”
Section: Molecular and Genetic Biomarkers Other Than Hormone And Her2mentioning
confidence: 99%
“…Additionally, this is the first time, to our knowledge, microglia were found to actively transport carcinoma cells 23 .…”
Section: Discussionmentioning
confidence: 58%
“…These findings indicate that glioma cells stimulate microglial cells to increase breakdown of extracellular matrix by induction of MMP-2 and thereby promote tumour invasiveness (Markovic, Glass, Synowitz, Rooijen, & Kettenmann, 2005). In consistency, it was reported that microglia promote brain colonisation of MCF-7 cells in a Wnt-dependent manner (Pukrop et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…Microglia, the resident macrophages of the central nervous system, play central roles in neurodegenerative and neuroinflammatory responses (Pukrop et al, 2010). There is 75 compelling evidence that microglia contribute to cerebral malignancies (Pukrop et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation